2020
DOI: 10.1002/pssb.201900657
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Negative Compressibility between 3D Cellular Models Constructed by 2D Hinging Wine‐Rack and Hexagonal Honeycomb Mechanisms

Abstract: Herein, two kinds of 3D hexagonal honeycomb equivalent models are proposed, enlightened by the octahedron model constructed by the wine‐rack mechanism. They differ in their unit‐cell arrangement forms, which are array and homogeneous arrangements, respectively. Referring to the analysis of the octahedron model, the expressions of compressibility properties of the two new models are given and the conditions for obtaining negative compressibility are analyzed. Comparing these two models with the octahedron model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 31 publications
0
12
2
Order By: Relevance
“…Take a look at all three directions, it can be found that the NLC of the monoclinic octahedral model in three directions are not exactly the same, but they can simultaneously produce negative compressibility in any two directions under certain conditions. It is clearly different from the orthorhombic and tetragonal models studied previously, [ 3,33–35 ] which can simultaneously exhibit negative compressibility in the OX 1 and OX 2 directions for any conditions, and have a completely opposite angle range from the OX 3 direction. Figure 6a shows the conditions to obtain zero compressibility in the three directions, in which the red, blue, and green lines represent the model obtaining zero compressibility in the OX 1 , OX 2 , and OX 3 , respectively.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Take a look at all three directions, it can be found that the NLC of the monoclinic octahedral model in three directions are not exactly the same, but they can simultaneously produce negative compressibility in any two directions under certain conditions. It is clearly different from the orthorhombic and tetragonal models studied previously, [ 3,33–35 ] which can simultaneously exhibit negative compressibility in the OX 1 and OX 2 directions for any conditions, and have a completely opposite angle range from the OX 3 direction. Figure 6a shows the conditions to obtain zero compressibility in the three directions, in which the red, blue, and green lines represent the model obtaining zero compressibility in the OX 1 , OX 2 , and OX 3 , respectively.…”
Section: Discussioncontrasting
confidence: 89%
“…To better produce negative compressive deformation, the model should be set as idealized hinging model, but the bending and tensile deformation of rods cannot be avoided in practice. Therefore, as we previously set, [ 35 ] the joints between rods in this work are also connected through flexible hinge, which can enhance hinging deformation as much as possible and weaken bending and tensile deformation. The unit‐cell can be clearly shown in Figure 1b and the details of the flexure hinge can be observed in Figure 1c.…”
Section: The Hinging Wine‐rack Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] Since Baughman et al [21] first proposed this property, it has gradually attracted widespread attention owing to its unconventional mechanical properties. Thus far, a large number of micromaterials [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and macrostructures [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] have been proved to exhibit negative compressibility. As for micromaterials, negative compressibility has been found to occur in a much greater variety of materials, ranging from molecular, [22,23] metal-organic frameworks (MOFs), [24,25] and polymers.…”
Section: Introductionmentioning
confidence: 99%